2021
DOI: 10.1007/s00259-021-05650-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging biomarkers of immune-related adverse events in immune-checkpoint blockade-treated metastatic melanoma patients: a pilot study

Abstract: Purpose To develop quantitative molecular imaging biomarkers of immune-related adverse event (irAE) development in malignant melanoma (MM) patients receiving immune-checkpoint inhibitors (ICI) imaged with 18F-FDG PET/CT. Methods 18F-FDG PET/CT images of 58 MM patients treated with anti-PD-1 or anti-CTLA-4 ICI were retrospectively analyzed for indication of irAE. Three target organs, most commonly affected by irAE, were considered: bowel, lung, and thyroid.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For patient recruitment, the inclusion criteria outlined in the study protocol facilitated the selection of patients at each study site that matched the target population. To homogenise data collection, we introduced a centralised platform with data collected in a relational database within the existing Networks of Imaging eXcellence (NIX) infrastructure, used in other multi-centre studies [ 25 ]. NIX allows homogenisation of the processes for acquisition and collation of patient imaging and other clinical data and provides a legal, ethical and logistic framework for linking geographically, politically and functionally disparate data sets with each other, and provides an environment for cross-validation of derived biomarkers and models.…”
Section: Resultsmentioning
confidence: 99%
“…For patient recruitment, the inclusion criteria outlined in the study protocol facilitated the selection of patients at each study site that matched the target population. To homogenise data collection, we introduced a centralised platform with data collected in a relational database within the existing Networks of Imaging eXcellence (NIX) infrastructure, used in other multi-centre studies [ 25 ]. NIX allows homogenisation of the processes for acquisition and collation of patient imaging and other clinical data and provides a legal, ethical and logistic framework for linking geographically, politically and functionally disparate data sets with each other, and provides an environment for cross-validation of derived biomarkers and models.…”
Section: Resultsmentioning
confidence: 99%
“…On FDG PET/CT, irAEs are characterized by increased uptake of FDG in the affected organ, and subsequent reduction in uptake indicates remission of acute inflammation, meaning that it can be radiographically manifested to a certain extent [101]. Therefore, 18 F-FDG PET/CT is a sensitive method for recognizing inflammatory processes that can be reflective of irAEs (Table 3) [102].…”
Section: Pet Molecular Imaging For Assessing Immune-related Adverse E...mentioning
confidence: 99%
“…The optimal percentiles for identifying irAEs were as follows: intestinal (SUV: 95%), lungs (SUV: 95%), and thyroid (SUV: 75%). This study provides more accurate PET-based prediction information for the occurrence of irAEs in melanoma patients treated with ICIs [102]. The introduction of artificial intelligence (AI) analysis methods provides quantitative and high-throughput information for PET imaging to effectively detect irAEs.…”
Section: Pet Molecular Imaging For Assessing Immune-related Adverse E...mentioning
confidence: 99%
“…However, the utility of 18 F-FDG PET/CT imaging in irAEs screening and monitoring is largely under-recognized currently (2). 18 F-FDG PET/CT imaging may be a sensitive method to identify the development and severity of irAEs, which usually present as a new non-neoplastic lesion with increased FDG accumulation after ICI treatment (56). For instance, elevated thyroid SUVmax commonly suggests ICI-related thyroiditis (57), while a diffuse increase of FDG uptake in the pancreas is a characteristic manifestation of ICI-related pancreatitis (58).…”
Section: Assessment Of Iraesmentioning
confidence: 99%
“…A study on patients with metastatic melanoma treated with ICIs found that novel quantitative imaging biomarkers, i.e. the SUV percentiles (SUV X% ) of 18 F-FDG uptake within the target organs, could be predictive of irAEs in the bowel, stomach, and thyroid ( 56 ). This study also demonstrated that some irAEs could be detected on 18 F-FDG PET/CT imaging before the onset of clinical symptoms, which showed increased 18 F-FDG uptake in the affected organs.…”
Section: Application Of 18 F-fdg Pet/ct Imaging In...mentioning
confidence: 99%